Leveraging Google Maps and Generative AI for Geography Education: Insights for Special Needs Students - Lestyono, Era Fazira; Solihin , Annas; Rachmadyanti , Putri; Kristanto, Andi; Dwinata, Algi (LPPI Yayasan Almahmudi bin Dahlan, 2024)
Integrating advanced technologies such as Google Maps and Generative AI is revolutionizing inclusive geography education by addressing the unique needs of students with speech delays and slow learning. This study examines the impact of these tools through interactive, technology-driven activities designed to boost engagement and comprehension of geographical concepts. Results indicate that 85% of students demonstrated heightened engagement and a 30% improvement in spatial reasoning skills. Collaborative tasks, including group discussions and presentations, enhance language development and cultivate cultural and social awareness. The multi-sensory features of Google Maps accommodate diverse learning styles, offering an enjoyable and effective educational experience. These findings underscore the transformative potential of technology in inclusive education, emphasizing the need for adaptive and supportive learning environments to empower students with special needs.